Dung beetle assemblages, dung removal and secondary seed dispersal: data from a large-scale, multi-site experiment in the Western Palaearctic - Tanja Milotić; Christophe Baltzinger; Carsten Eichberg; Amy E. Eycott; Marco Heurich; Jörg Müller; Jorge A. Noriega; Rosa Menendez; Jutta Stadler; Réka Ádám; Tessa Bargmann; Isabelle Bilger; et al. (Frontiers of Biogeography)
By manipulating faeces during feeding and breeding, dung beetles (Coleoptera: Scarabaeidae) fulfil important ecosystem functions in terrestrial ecosystems throughout the world. In a pan-European multi-site experiment (MSE), we estimated the ecosystem functions of dung removal and secondary seed dispersal by differing combinations of dung beetle functional groups. Therefore, we classified dung beetles into five functional groups according to their body size and dung manipulation method: dwellers, large and small tunnelers, and large and small rollers. Furthermore, we set up a dung beetle sampling database containing all sampled dung beetles during the project. By identifying dung beetle specimens to the species level, we obtained a detailed insight into the dung beetle communities at each study location. By establishing experimental plots allowing and inhibiting specific combinations of functional groups in the local dung beetle assemblage from removing dung and seeds, we estimated the role of each group in dung removal and secondary seed dispersal during a 4-week period. We performed all experiments in grazed (semi-)natural grasslands, and used different dung types (cattle, horse, sheep, goat or red deer) to match the herbivore species grazing in close vicinity of each of the study areas. Simultaneously, we sampled dung beetle assemblages by using pitfalls baited with the same dung types as used in the experiments. This data paper documents two datasets collected in the framework of this MSE project. All the experiments took place between 2013 and 2016 at 17 study sites in 10 countries and 11 biogeographic zones. The entire dung beetle sampling dataset was published as a sampling event dataset at GBIF. The dataset includes the sampling results of all 17 study sites, which contain 1,050 sampling events and 4,362 occurrence records of 94 species. The second dataset contains the results of the dung removal and secondary seed dispersal experiments in which we used 11 experimental treatments and the five dung types mentioned above. This experimental results dataset holds all experimental results of the MSE project (11,537 records), and was published in the online data repository Zenodo.